التصنيع الحيوي لجسيمات الفضة النانوية باستعمال مستخلص نباتmoringa oliefera - حوري, إكرام; مداني, نجلاء (universty of elouedجامعة الوادي, 2020)
"الملخص يهدف هذا العمل الى استخدام نبات المورينجا الوفيرا لدراسة مدى قابيلتها لتحضير AgNPs حيث بينت النتائج ان اضافت محلول AgNO3بتركيز 1Mmعند5.4 pH وT=95°Cللمستخلص يتغير لونه الى اللون البني تمت دراسة طيف الامتصاص UV.V لمحلول AgNPs كخطوة ثانية لتاكد من الجسيمات وتبين انه تقع على طول موجي 450 نانومتر ما تبين ان قمم حيود الاشعة X و(111) (220)و(311) عند الزوايا على التوالي (77,28;64,34;44,19;38,00) تبين ان المحلول AgNPs ذا تاثير تثيطي واضح على ست انواع بكتيريا ذات مقاومة متعددة حيث بلغ اكبر قطر تثبيط لبكتيريا Proteus vulgaris و بكتيريا Staphylococcus aureus أي بمتوسط (30.3± 1.11) و 30.3) ± 0.71 ) ثم تليها Klebsiella pneumoniae (24 ± 0.91) ثم Escherichia coli (23.3 ± 0.48) ثم Bacillus cereus (23.3 ± .0.75) و. epidermidis S (19 ± 0.41) ""Abstract The aim of this work is using the plant Moringa oliviera to study its ability as reducing agent to prepare silver particales. The result showed that adding AgNO3 solution 1mM to the extract changed color to brown The spectrum of silver nanoparticles solution using Uvi,vis Spectroscopy was used as a second step to confirm the production of nanoparticls ,Results showed that the absorbance at 450 nm also the X-ray diffraction showed peaks at(111) (220) (311) at the diffraction angles (77,28;64,34;44,19;38,00 ) respectively .The result showed that AgNO3 solution has inhibitory effect against six different bacterial which are Escherichia coli Klebsiella pneumoniae, Proteus vulgaris, Staphylococcus aureus and S. epidermidis, Bacillus cereus, that their inhibitory diameter is: for Escherichia coli(23, 22, 24, 24) , Klebsiella pneumonia(29, 31, 33, 28), Proteus vulgaris(25 ,26, 23, 22 ), Staphylococcus aureus(29, 32, 29, 30) and S. epidermidis(20, 19, 18, 19 ), Bacillus cereus(21, 24 ,25 ,22 ). "
مذكرة تخرج ماستر كيمياء
Keywords: الكلمات الدالة:المورنجا الوفيرا, جسيمات الفضة النانونية , طيف الامتصاص ,UV V الاشعة X ,البكتيريا; Key words: Moringa oliefera , Uvi,vis Spectroscopy ,the X-ray, bacterial